When Motivated Responses to Threat Backfire: Risky Socializing During the COVID-19 Health Crisis. Issue 5 (July 2022) - Forsyth, Rachel B.
This research examined the relationship between psychological processes that help individuals cope with challenging circumstances and their failure to act to reduce the likelihood and severity of the challenge itself. In two cross-sectional studies of U.S. residents ( N = 621) conducted during the COVID-19 pandemic, individuals' motivated responses to threat predicted their noncompliance with directives prohibiting risky socializing: Those who perceived the disease to be a threat to their health were more likely to engage in risky socializing if they avoided information about the pandemic or they exhibited a dispositional tendency to join with other people when stressed. Several alternative causal sequences can account for these findings, but one suggests that the risky socializing during the COVID-19 pandemic was due, in part, to people's psychological reaction to threat; as people responded to minimize their distress, they inadvertently increased their risk of contracting the illness.